Robert Duncan, Kabbalah, and “The Dominion of the Poetic Mind” - Norman Finkelstein (Sillages Critiques)
What leads poets into mystical, hermetic and occult studies? How do these traditions shape their poetic practice, and conversely, how do their poems deepen our understanding of the enduring power of these bodies of thought, belief, and ritual? In response to these questions, this paper focuses on Robert Duncan’s study of Kabbalah, especially Kabbalistic language mysticism, which he reads as “the description of the process of a poem.” For Duncan, the language magic of Kabbalah is an important model of poetic language – which is in itself magical. “By associations, by metaphor, by likeness of the part, by fitting as part of a larger figure, by interlinking of members, by share, by equation, by correspondence, by reason, by opposition, by pun or rhyme, by melodic coherence,” Duncan, as he writes in The H.D. Book, seeks to take us to a place “where the image becomes informed, from above or below, and takes over as an entity in itself, a messenger from a higher real.” Situating Duncan as the heir to nineteenth-century occult organizations and the rethinking of hermetic traditions in groups such as the Order of the Golden Dawn, I then proceed to a brief reading of his poem “Roots and Branches,” in order to demonstrate how Duncan’s kabbalistic vision of the “imaginary tree of the living in all its doctrines” awakens “transports of an inner view of things,” and secures the poetic imagination as the supreme vehicle of mystical experience.